Determinants of Independent Audit Opinions: Evidence From Hose-Listed Firms - Lam, Nguyen Thanh; Dat, Nguyen Thanh (INTERNATIONAL JOURNAL OF TRENDS IN ACCOUNTING RESEARCH, 2025)
This study investigates the factors influencing independent auditor opinions on the financial statements of companies listed on the Ho Chi Minh Stock Exchange (HOSE). Using a sample of 413 firms spanning 2020–2024 (2,065 firm-year observations), the research employs logistic regression to examine the impact of nine financial and non-financial variables. The model yields statistically significant results (F = 2.56, Sig = 0.048, R² = 0.0591), with six out of nine hypotheses supported. Specifically, current ratio, fixed asset turnover, inventory turnover, debt ratio, audit firm size, and the proportion of non-executive board members significantly influence audit opinions. Audit firm size and board independence exhibit the most pronounced effects among these. In contrast, return on equity (ROE), revenue growth, and audit report lag do not show significant associations, diverging from findings in prior literature. The modest explanatory power of the model (R² = 5.91%) highlights the challenge of capturing audit opinion determinants in an emerging market context. The study suggests that firms improve liquidity, asset efficiency, and corporate governance while aligning with larger firms to enhance audit outcomes. Audit firms are encouraged to strengthen their technical capacity and governance assessments. Regulatory bodies are advised to promote board independence, monitor financial leverage, and accelerate IFRS implementation.